Novel penguin Avian avulaviruses 17, 18 and 19 are widely distributed in the Antarctic Peninsula. Issue 6 (15th August 2019) - Olivares, Florencia; Tapia, Rodrigo; Gálvez, Camilo; Meza, Fernanda; Barriga, Gonzalo P.; Borras‐Chavez, Renato; Mena‐Vasquez, Juan; Medina, Rafael A.; Neira, Victor
Abstract: Three novel Avian avulavirus species were discovered and isolated during 2017 from Gentoo penguins ( Pygoscelis papua ) at Kopaitic island in the Northwestern region of the Antarctic Peninsula. The viruses were officially named as Avian avulavirus 17 (AAV17), Avian avulavirus 18 (AAV18) and Avian avulavirus 19 (AAV19), collectively referred to as penguin avulaviruses (PAVs). To determine whether these viruses are capable of infecting the three species of Pygoscelis spp. penguins (Gentoo, Adelie and Chinstrap) and assess its geographical distribution, serum samples were collected from seven locations across the Antarctic Peninsula and Southern Shetland Islands. The samples were tested by Hemagglutination inhibition assay using reference viruses for AAV17, AAV18 and AAV19. A total of 498 sera were tested, and 40 were positive for antibodies against AAV17, 20 for AAV18 and 45 for AAV19. Positive sera were obtained for the penguin's species for each virus; however, antibodies against AAV18 were not identified in Adelie penguins. Positive penguins were identified in all regions studied. Positive locations include Ardley Island and Cape Shirreff at Livingston Island (Southern Shetland Region); Anvers Island, Doumer Island and Paradise Bay in the Central Western region; and Avian Island at Southwestern region of the Antarctic Peninsula. The lowest occurrence was observed at the Southwestern region at Lagotellerie Island, where all samples were negative. On the other hand, Cape Shirreff and Paradise Bay showed the highest antibody titres. Field samples did not evidence cross‐reactivity between viruses, and detection was significantly higher for AAV19 and lower for AAV18. This is the first serologic study on the prevalence of the novel Avian avulaviruses including different locations in the white continent. The results indicate that these novel viruses can infect the three Pygoscelis spp. penguins, which extend across large distances of the Antarctic Peninsula.